Your Google game plan for success : increasing your web presence with Google AdWords, Analytics and Website Optimizer - Teixeira, Joe. (Indianapolis, IN : Wiley Pub., 2010)
Presents strategies for writing a successful Internet advertising campaign using Google AdWords and explores the technology of Google Analytics and Google Website Optimizer.
Includes index.
Keywords: Internet searching -- Statistical services; Web usage mining -- Computer programs; Internet users -- Statistics -- Data processing; Internet marketing